L’engagement comportemental des enseignants lors d’une formation à distance : une enquête dans la fédération Wallonie-Bruxelles - Audrey Kumps; Sabrin Housni; Karim Boumazguida; Gaëtan Temperman; Bruno De Lièvre (Humanités Numériques)
In 2018, the Government of French-speaking Belgium adopted a digital strategy which emphasises the need to invest in education through and in digital skills to give all citizens the ability and the means to act. Nevertheless, we note that teachers only integrate digital tools in their teaching practices to a limited extent and face many difficulties. To help them overcome these difficulties, we have proposed 230 teachers a connectivist distance learning training. This study exploits the various analytics collected during the learning process to measure the behavioral engagement during this type of training. Using a clustering approach, our results highlight three profiles of engagement in the learning environment. They allow us to formulate several recommendations that can guide the design and regulation of training sessions for teaching new digital skills.